EASTERN RUMELIA EVENTS IN THE AMERICAN PRESS (1878-1888) - Karakoc, Ercan; Durak, Gokhan (TRAKYA UNIV BALKAN YERLESESI ENSTITULER BINASI, 2020)
The Ottoman Empire was in the process of disintegration in the 19th century. The non-Muslim nations living in the Balkan geography under the Ottoman rule began to rebel with the influence of nationalist thoughts. The Bulgarians started to gain power in the process with the support of the Russia and took important steps towards independence. According to the Treaty of San Stefano signed after the Ottoman-Russian War of 1877-1878, it was envisaged to establish a large independent Bulgarian Kingdom. In the face of this development, which would allow Russia to reach its goal of landing on the warm seas through Bulgaria and to have absolute advantage over the Balkans, the Great Powers particularly Britain, intervened and a new treaty was made in Berlin. With the Treaty of Berlin, an Autonomous Bulgarian Principality, whose borders were narrowed was established and the Eastern Rumelia Province under the Ottoman rule was formed. The Bulgarians rebelled in Plovdiv with an attempt to weaken Ottoman influence in Eastern Rumelia in order to put the region under the rule of the Bulgarian Principality. There were conflicts in the region and the events were closely followed by the foreign press. As a matter of fact, it was seen that the events of Eastern Rumelia were followed in all dimensions by the American press and the newspapers mostly include news and comments in favor of the Bulgarians. This is also important that it indicates the political and economic interest of the United States towards the Ottoman geography.
Keywords: American Press; Balkans; East Rumelia; Ottoman Empire; Bulgarians; Area Studies